Auxiliary equation will be
"(m-2)(m+3)=0"
"m_1=2, m_2=-3"
Hence
"P.I.=\\dfrac{1}{D^2+DD'-6D'^2}y\\sin x"
"=I.P.\\ of\\ e^{ix}\\dfrac{1}{(D+i)^2+(D+i)(D'+0)-6(D'-0)^2}y"
"=I.P.\\ of\\ e^{ix}\\dfrac{1}{D^2-1+2iD+DD'+iD'-6D'^2}y"
"=I.P.\\ of\\ e^{ix}\\dfrac{1}{D^2+DD'-6D'^2+i(2D+D')-1}y"
"=I.P.\\ of\\ -e^{ix}\\dfrac{1}{1-[D^2+DD'-6D'^2+i(2D+D')]}y"
Using binomial expansion
"=I.P.\\ of\\ -e^{ix}(y+i)"
"=I.P.\\ of\\ -(\\cos x-i\\sin x)(y+i)"
"P.I.=-\\cos x-y\\sin x"
Hence the general solution is given by
Comments
Leave a comment